PRODUKSI GLUKOAMILASE DARI RHIZOPUS ORVZAE L16 PADA MEDIA PATI SAGU (METROXYLON) YANG MENGANDUNG EKSTRAK TAUGE - Yetti M.lskandar; Linar Z.Udin; A. T. Karossi (Jurnal Kimia Terapan Indonesia, 1994)
Glucoamylase production from Rhlzopus oryzae L16 has been carrried out in a fermentation medium using sago (Metroxylon sp) starch. Various levels of mung bean sprout extract (1% - 5%) was added into the medium as vitamin source. The fermentation process was carried out at 30°C in aerobic condition with an agitation rate of 120 rpm and for five days. The results of the fermentation was compared with an other fermentation medium containing malt extract 3%. The glucoamylase specific activity of 4500 Unitslg protein, starch consumption of 62.5% and biomass produced of 2.93 g dry weighill: medium were demonstrated with the latter medium. It was found that media which contained 4% mung bean sprout extract had maximum glucoamylase specific activity of 19720 Unitslg protein at day-3. The enzyme activity was assayed at 55°C with incubation time 10 minutes. At this third day of fermentation the starch utilization reached 55.5% and the biomass production was 3.12 g dry weight/L medium.